2011
DOI: 10.1002/adma.201101622
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/Carbon Nanotube Hybrid‐Based Transparent 2D Optical Array

Abstract: Graphene/carbon nanotube (CNT) hybrid structures are fabricated for use as optical arrays. Vertically aligned CNTs are directly synthesized on a graphene/quartz substrate using plasma-enhanced chemical vapor deposition (PECVD). Graphene preserves the transparency and resistance during CNT growth. Highly aligned single-walled CNTs show a better performance for the diffraction intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…In addition, the optical properties of G-CNTs also aroused much attention. For example, Kim et al [18] fabricated G-CNT transparent 2-dimensional optical array and researched its holographic property.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the optical properties of G-CNTs also aroused much attention. For example, Kim et al [18] fabricated G-CNT transparent 2-dimensional optical array and researched its holographic property.…”
Section: Open Accessmentioning
confidence: 99%
“…For example, Dong et al [19] synthesized highly conductive G-CNTs using copper as catalyst under ethanol. Kim et al [18] fabricated G-CNTs using Al and Fe as catalysts under Ar, H 2 and C 2 H 2 gas atmosphere. Very recently, we synthesized reduced graphene oxide-CNT hybrid materials (RGO-CNTs) by a facile and catalyst-free route, and found that the weight ratio of CNTs to RGO can be adjusted in a relatively wide range of 0.33 to 7.039 by regulating the annealing temperature [20].…”
Section: Open Accessmentioning
confidence: 99%
“…However, graphenes prepared by using conventional approaches are usually lying down on substrates. The typical strategies are chemical or mechanical exfoliation [1,19], chemical vapor deposition (CVD) [20,21], and epitaxial growth on SiC [22], these flat-lying graphenes are Page 3 of 26 A c c e p t e d M a n u s c r i p t believed to have poor FE performance because their large aspect ratios can not be fully exploited [12], which puts a huge demand for the fabrication of aligned graphenes. Previous works have proven that plasma enhanced chemical vapor deposition (PECVD) is an effective way to synthesize vertical graphenes [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, among FET-based non-volatile memory devices, the ferroelectric FET, an important type of memory cells without a storage capacitor, is significantly attractive for memory and switch applications, because of the wide range of its interesting features, including small cell size, non-destructive read-out, low-power consumption, good retention and fast response time [815]. Another example of emerging applications based on LCs is holography, which is an ideal technology to realize three-dimensional (3D) dynamic images by changing the refractive index [16,17]. However, unfortunately, photo-refractive materials and photo-chromic materials require high external voltages and long response times, respectively, to modulate the refractive index [1822].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid such difficulties, arrays of carbon nanotubes (CNTs)/nanofibers were introduced to locally modulate the refractive index of the LC medium at low operation voltages [2325]. Recently, we also developed a transparent, active-type 2D optical array that operates at low voltage using a graphene/CNT hybrid structure instead of using opaque metals [16]. In addition to demonstrating proof-of-principle concepts for individual single LC device applications, it is also possible to achieve technological advances and revolution into a rapidly growing multidisciplinary field involving displays, electronics and energy harvesting to integrate displays into a self-powered system [26,27].…”
Section: Introductionmentioning
confidence: 99%